2021
DOI: 10.1016/j.ekir.2021.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Outcome of Secondary Steroid-Resistant Nephrotic Syndrome in Chinese Children

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…The study showed that the clinical features of secondary steroid resistance with respect to gender, age and blood pressure was similar compared to secondary SRNS reported in previous studies. 2 A complete or partial response to therapy in the first year after being diagnosed as secondary SRNS did not show any relation with respect to progression to CKD. The predominant histological finding of MCD in patients was similar to a previous study.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…The study showed that the clinical features of secondary steroid resistance with respect to gender, age and blood pressure was similar compared to secondary SRNS reported in previous studies. 2 A complete or partial response to therapy in the first year after being diagnosed as secondary SRNS did not show any relation with respect to progression to CKD. The predominant histological finding of MCD in patients was similar to a previous study.…”
Section: Discussionmentioning
confidence: 81%
“…The predominant histological finding of MCD in patients was similar to a previous study. 2,3,12 Other studies related to primary SRNS reported FSGS as the primary finding. 4,8 CR and PR at 1 year the current study was similar to a study which reported CR 71.4% and PR 16%, while a multicentre study reported a remission rate of 69%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prognosis of primary FSGS varies according to its response to GCs ( Mason et al, 2020 ; Zhao and Liu, 2020 ). Steroid-resistant FSGS is an independent risk factor for decreased renal function ( Rosenberg and Kopp, 2017 ; Ying et al, 2021 ). At present, the main methods for the treatment of MCD, FSGS, and MN include angiotensin-converting enzyme inhibitors or angiotensin receptor blockers, steroid hormones, CNIs (cyclosporine or tacrolimus), cyclophosphamide, or CD20 monoclonal antibody.…”
Section: Protective Effects Of Traditional Chinese Medicine and Activ...mentioning
confidence: 99%
“…For the genetic subgroup of SRNS, complete remission is more uncommon. Around 20% of genetic SRNS patients have chronic kidney disease (CKD), progress to kidney failure (KF) (Trautmann et al, 2023 ) and no response to immunosuppression in the first year is a predictor of poor kidney function outcomes (Ying et al, 2021 ). The most common histological diagnoses in children with NS include minimal change disease (MCD), focal segmental glomerulosclerosis (FSGS), membranoproliferative glomerulonephritis and membranous glomerulonephritis (Churg et al, 1970 ).…”
Section: Introductionmentioning
confidence: 99%